Industry 4.0: a systematic review in technical and vocational education and training - Siti Zaharah,; Mohd Nasir Selamat,; Khadijah Alavi,; Kadir Arifin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Industry 4.0 is the digital transformation of industrial markets (industrial transformation) with smart manufacturing currently on the forefront. For this reason, Industry 4.0 is a new industrial reform that has been linked to industrialization studies, initiated high-tech strategy, real-time data processing and cyber-physical systems. The main goal of this paper is to address the gaps by studying in depth the research articles from different journals and conferences on the topic of Industry 4.0 in technical and vocational education and training (TVET), thus making it easier for future references. This study centered on incorporating the articles published in the recent years to establish knowledge on the topic, further identifying areas for future research. Hopefully, from this report, technical and vocational students would be exposed to new inventions of technology revolution as well as to create the innovative worker for a better future. In addition, this paper offers a set of guidelines to policy makers for the successful integration of Industry 4.0 in TVET.